The curriculum of Sheik Ismail bin Ahmed Al-Hiri(430AH) in his book and faces of Koran - Mohammed, Omar Ibrahim (Al-Adab Journal, 2022)
In this study, I tried to research the approach of Sheikh Ismail bin Ahmed Al-Hairy in his book (Faces of the Qur’an), which is considered the widest and most important literature that is concerned with revealing and clarifying Qur’anic words, with multiple connotations, including sometimes special cognates or connotations and metaphorical meanings or synonymous meanings that can be identified The context and its intent at other times, and that limiting the book to certain words that are collected by a specific link, is considered one of the curriculum, and the author has excelled in presenting his material, and he mentioned some of it in the introduction, which reduced the difficulty for the reader, and the research tried to explain the book’s approach in presenting the material, and in An analysis of the significance of the Qur’anic words, united in their words, which revolved around different meanings, so it was based on an introduction in which we spoke on the content of the research, and a statement of the plan that the researcher followed in presenting the divisions of the research subject